The Role of Good Governance for Economic Growth in ASEAN - Sapanang, Baso Aditya; Fitrianti, Retno; Yakub, Andry Irawan; Sopian, Andi; Hamka, Hamka; Fitrianti, A. Nur (Asian Journal of Management Analytics, 2024)
The role of the government in implementing Good Governance or effective government management is to strive for the improvement of a country's economic growth towards a better direction. Good governance quality will create efficient market mechanisms, hence promoting sustainable economic growth. The purpose of this study is to analyze the impact of government governance on economic growth in the ASEAN-6 countries. The data in this study is sourced from the Worldwide Governance Indicator provided by the World Bank. Using cross-sectional data from 6 ASEAN countries and time series data over the period 2006-2020. The best model for panel data regression is the Fixed Effect Model (FEM). Based on the findings of this study, it was determined that the variable with no significant impact on economic growth in the 6 ASEAN countries is government effectiveness. Meanwhile, the variables of rule of law, control of corruption, and political stability and lack of violence /terrorism has a significant influence on economic growth in the 6 ASEAN countries.